Beyond the Ivory Tower: Exploring University Social Responsibility through the Lens of Tunisian Higher Education Leaders - Kilani, Fatma; Zaiem, Imed; Edrees, Hussein N. E.; Sobaih, Abu Elnasr E. (International Journal of Innovative Research and Scientific Studies, 2025)
Social Responsibility (SR) is increasingly vital in the daily operations of higher education institutions (HEIs) as it affects HEIs’ brand and students’ intention to join such HEIs. However, in the proliferation of this concept and its effective application in student and academic life, a gap exists in understanding this issue in developing nations, i.e., Tunisia. The main objective of this research is to study the perceptions of university social responsibility (USR) by heads of Tunisian higher education institutions using stakeholder theory. A qualitative study was undertaken with public and private Tunisian HEIs, using an interview guide to understand the perceptions of USR. The results showed that a minority of academic institutions gives remarkable interest to the USR, mainly private sector institutions. Additionally, heads agreed that social responsibility should be a priority for all HEI actors performing in this way in their behavior. These socially responsible behaviors are grouped into four dimensions as perceived by HEI heads: responsibility to internal stakeholders, ethical responsibility, philanthropic responsibility, and commitment to the community. The results confirm the role of USR in achieving universities’ missions beyond education and scientific research.